Emergency department contact prior to suicide in mental health patients. Issue 6 (26th July 2010) - Da Cruz, D; Pearson, A; Saini, P; Miles, C; While, D; Swinson, N; Williams, A; Shaw, J; Appleby, L; Kapur, N
Abstract : Objectives: To describe attendance at emergency departments (EDs) in the year prior to suicide for a sample of mental health patients. To examine the characteristics of those who attended (particularly those who attended frequently) prior to suicide. Design: Case review of ED records for 286 individuals who died within 12 months of mental health contact in North West England (2003–2005). Method: Cases identified through the National Confidential Inquiry into Suicide were checked against regional EDs to establish attendance in the year prior to death. Records were examined to establish the number of attendances, reason for the final, non-fatal attendance, treatment offered and outcome. Results: One hundred and twenty-four (43%) individuals had attended the ED at least once in the year prior to their death, and of these, 35 (28%) had attended the ED on more than three occasions. These frequent attenders died by suicide significantly sooner after their final, non-fatal attendance than other attenders. A clinical history of alcohol misuse was also associated with early death following ED attendance. Conclusions: Over 40% of our clinical sample attended an ED in the year prior to death, and some individuals attended particularly frequently. EDs may therefore represent an important additional setting for suicide prevention in mental health patients. The majority of attendances prior to suicide were for self-harm or to request psychiatric help. Clinicians should be alert to the risk associated with such presentations and to the possible association between frequent attendance and suicide.